Measurement of the two-photon excitation cross-section of the 6p′[3/2]2 and 6p′[1/2]0 levels of Xe I at the wavelengths 224.3 and 222.6 nm. (26th July 2021) - Drag, C; Marmuse, F; Blondel, C
Abstract: The two-photon excitation cross-section is a key parameter for the two-photon absorption laser induced fluorescence (TALIF) method, which is commonly used to measure atomic densities in gaseous media, especially for plasma diagnostics. The method consists in recording the fluorescence signal that follows the resonant absorption of two photons of UV light. Calibration often relies on comparing the signal recorded in the studied sample with the fluorescence produced, at a similar wavelength, in a noble gas vapor, the density of which can be easily known. The ratio of the involved cross-sections however plays an essential role for the accuracy of such measurements. Yet the two-photon excitation cross-section of atomic xenon, which is often used as the reference for oxygen density measurements, was measured only once, at the wavelengths of interest. The aim of the present study has been to consolidate the experimental value of that key parameter. The cross-section is found equal to 1.3 6 − 0.34 + 0.46 and 1.8 8 − 0.54 + 0.75 × 1 0 − 43 m 4 for the 6 p ′[3/2]2 and 6 p ′[1/2]0 levels, respectively. For the 6 p ′[3/2]2 level this is more than twice smaller than previously admitted. Even though the necessarily large relative uncertainty of a non-linear cross-section attaches a relatively large uncertainty to this factor of one half, the result suggests that atomic densities already measured by Xe-calibrated TALIF may have to be revised to significantly lower values. The experiments performed also provide an opportunity to revisit the validity of the approximations used for quantitative TALIF measurements and the collisional broadening and pressure shift of the two-photon 6 p ′[1/2]0 line. A new formula has been used to describe the two-photon absorption of a Gaussian beam in a long gas cell, which makes the decrease of the beam intensity a simple analytic expression even in strong absorption regime, based on a polylogarithmic function of the absorption rate variable.